Development of novel, exon‐primed intron‐crossing (EPIC) markers from EST databases and evaluation of their phylogenetic utility in Commiphora (Burseraceae)1. (31st March 2014) - Gostel, Morgan R.; Weeks, Andrea
Abstract : Premise of the study: Novel nuclear exon‐primed intron‐crossing (EPIC) markers were developed to increase phylogenetic resolution among recently diverged lineages in the frankincense and myrrh family, Burseraceae, using Citrus, Arabidopsis, and Oryza genome resources. Methods and Results: Primer pairs for 48 nuclear introns were developed using the genome resource IntrEST and were screened using species of Commiphora and other Burseraceae taxa. Four putative intron regions ( RPT6A, BXL2, mtATP Synthase D, and Rab6 ) sequenced successfully for multiple taxa and recovered phylogenies consistent with those of existing studies. In some cases, these regions yielded informative sequence variation on par with that of the nuclear ribosomal DNA internal transcribed spacer. Conclusions: The combination of freely available genome resources and our design criteria have uncovered four single‐copy nuclear intron regions that are useful for phylogenetic reconstruction of Burseraceae taxa. Because our EPIC primers also amplify Arabidopsis, we recommend their trial in other rosid and eudicot lineages.